THE POLITENESS OF TOUR GUIDES TO EXPLAIN TOURIST DESTINATION TO TOURISTS IN PURA MANGKUNEGARAN SURAKARTA (FOCUSED ON SPEECH ACT) - KHOTIMAH, ARUM WULAN NURUL; ALI, SOPYAN (Politeknik Harapan Bangsa Surakarta, 2020)
Indonesia is a tourist destination in the world that amaze the beautiful Nation. Indonesia has nature and historical tourist attraction. Many historical tourist attraction are found in central java especially in Solo. Solo has Surakarta palace, Pura Mangkunegaran, Radya pustaka museum, Monumen pers, Sangiran museum, etc. The writer interests to do research about